Eye of the beholder - McGregor, Ewan, 1971-; Judd, Ashley; Bergin, Patrick; Lang, K. D. (Kathy Dawn), 1961-; Priestley, Jason, 1969-; Bujold, Geneviève.; Elliott, Stephan; Destination Films; Behaviour Worldwide (Firm); Village Roadshow Pictures; Ambridge Enterprises; Hit & Run Films; et al. (Culver City, Calif. : Columbia TriStar Home Video, 2000)
The Eye is an intelligence agent whose current assignment is to track Joanna Eris, a woman suspected of blackmailing a senior government official. But the Eye soon learns that Eris is far more than a blackmailer.
Originally released as a motion picture in 1999.
Special features: director's commentary; production notes; talent files; theatrical trailers; scene selections.
Ewan McGregor, Ashley Judd, Patrick Bergin, K.D. Lang, Jason Priestley, Genevieve Bujold.
MPAA rating: R.
DVD; Dolby digital 2.1 surround.
In English with English, French and Spanish subtitles; closed-captioned.
Keywords: Feature films; Films for the hearing impaired